Fiscal policies, devaluations and exchange rate regimes: the stabilisation programmes of Ireland and Greece - Alogoskoufis, George S. (Economic & Social Studies, 1992)
This paper contrasts the stabilisation programmes of Ireland and Greece in the 1980s and draws out lessons for the design of such programmes in small open economies. Programmes relying on government revenue increases are judged to be less likely to succeed than those based on expenditure reductions. The contribution which devaluation in the initial stages of such a programme can make is also emphasised, but only in the context of a regime with established anti-inflationary credibility.
Keywords: Fiscal policy; Devaluation; Exchange rates; Ireland; Greece; Stabilisation